Rancangan Sistem Informasi Barang Inventaris Berbasis Website Pada Sekolah Tinggi Ilmu Manajemen Sukma - Siregar, Yulia Rahma; Rahim, Robbi (LPPM STIKOM Tunas Bangsa, 2024)
This research aims to design a website-based inventory information system at Sukma College of Management. This system is expected to assist in managing inventory data efficiently and effectively. The methodology used in this research includes requirements analysis, system design, implementation, and testing. The result of this research is an information system that is able to record, monitor, and report inventory items in real-time. The system is also equipped with search, grouping, and automatic notification features to facilitate inventory management. With this system, it is expected that the administration process of inventory goods at Sukma College of Management can run more structured and integrated, thereby increasing accuracy and efficiency in managing inventory data.